ANALISIS EFISIENSI SIKLUS TURBIN GAS MENGGUNAKAN SOFTWARE CYCLE TEMPO BERDASARKAN VARIASI PEMBEBANAN DI PT X - Muhammad Rafiian Arumbinang (2020)
Electricity demand will continue to increase over time. Therefore the amount of electricity produced needs to be increased. Besides the power plant must also develop in a better direction, one of which is to increase the efficiency of the power plant. Differences in loading on gas turbines are one of the way to improve the efficiency of gas turbines. In this study, using three types of loading variations, namely gas turbines with a load of 85 MW, 100 MW, and 120 MW. Data retrieval is done using digital data in the Central Control Room. The data is taken from operational data in May 2019-June 2019. The calculation process is carried out in theory and in numerically using Cycle Tempo Software. The results of this study indicate that each increase in load the efficiency of the gas turbine cycle also increases. In theory, the highest gas turbine cycle efficiency occurs in GT 2.3 gas turbines with a 120 MW loading which is 27.55%, while the lowest gas turbine cycle efficiency occurs in GT 2.1 gas turbines with 85 MW loading of 23.29%. In numeric, the highest gas turbine cycle efficiency occurs in the GT 2.3 gas turbine with a load of 120 MW, amounting to 27,549%, while the lowest gas turbine cycle efficiency occurs in the GT 2.1 gas turbine with an 85 MW loading of 23,949%.